Interactive 360-degree virtual reality: the acceptance among educators and learners in public higher education in Malaysia / Norsyuhada Ahmad Rashidi and Wardatul Hayat Adnan - Ahmad Rashidi, Norsyuhada; Adnan, Wardatul Hayat (Universiti Teknologi MARA, Kedah, 2024)
Due to a lack of resources, tools, and expertise among Malaysian educators, it is challenging to prepare software and applications for studying digital design content. Additionally, despite the completion of the knowledge transfer, there is still scepticism about its acceptance among instructors and students. As a result, the current study intends to investigate whether educators and students in public higher education in Malaysia are accepting of eLearning in digital book design. In the current study, a structured interview will be used, and participants will include educators from three (3) public universities in Malaysia: Universiti Teknologi MARA (UiTM), Universiti Pendidikan Sultan Idris, and Universiti Malaysia Kelantan (UMK). Between the instructors and students, there are 12 informants. Following the transcription process using the informants' data, the keywords used by the informants will next be categorised according to internal and external parameters. To accomplish this, all of the information gathered from the informants was analysed using thematic analysis. The study discovered challenges in using 360-Degree in virtual reality to teach the subject because of the accessibility of 360 software, the lack of supportive infrastructure, such as appropriate gear, and the high cost. Furthermore, educators' 360 learning knowledge and skills are lacking, which has affected how poorly they give lessons. Technology has advanced greatly in many industrialised nations, but in developing nations like Malaysia, where many people lack the necessary skills and readiness, this is still a problem.